Back Cover: Cover Image, Volume 75, Issue 1. Issue 1 (5th December 2018) - Morrison, William R; Blaauw, Brett R; Short, Brent D; Nielsen, Anne L; Bergh, James C; Krawczyk, Greg; Park, Yong‐Lak; Butler, Bryan; Khrimian, Ashot; Leskey, Tracy C
Abstract : The back‐cover image is based on the Research Article Successful management of Halyomorpha halys (Hemiptera: Pentatomidae) in commercial apple orchards with an attract‐and‐kill strategy by William R Morrison et al., DOI: 10.1002/ps.5156 . Photo Credit: Rob Morrison, Ph.D. Abstract : The back‐cover image is based on the Research Article Successful management of Halyomorpha halys (Hemiptera: Pentatomidae) in commercial apple orchards with an attract‐and‐kill strategy by William R Morrison et al., DOI: 10.1002/ps.5156 . Photo Credit: Rob Morrison, Ph.D.